DESAIN APLIKASI MANAJEMEN PUJA BAKTI BERBASIS WEB PADA VIHARA XYZ - Henry Felix Hartanto; Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
This research aims to design a web-based management application for handling the attendance and task management processes for XYZ Buddhist Temple. The current attendance registration process results in inefficiencies, such as long wait times during attendance registration, which causes inconvenience. This application will be designed using design thinking methodology which consists of 5 stages, such as Empathize, Define, Ideate, Prototype, and Test. By introducing QR code into attendance registration process, the application will ease the check-in process, enhance data accuracy, and provide real-time access to attendance records for the staff. Additionally, it improves the coordination of staff roles in organizing the puja bakti. The expected outcomes include increased operational efficiency, a reduction in errors associated with manual input, and more organized management of attendees and event-related tasks. This solution can also serve as a scalable framework for similar organizations looking to improve their event management processes.